New Copper and Oxomolybdate Robson-Type Polynuclear Macrocyclic Complexes: Structure, Spectroscopy, and Electrochemical Properties - Marcelo Carpes Nunes; Marcos Antonio Ribeiro; Fábio Souza Nunes (Journal of Chemistry)
The polynuclear complexes [Mo3O8(tidf)]·dmso·2H2O (1) and [{Cu2(tidf)}2(μ-Mo8O24)] (2) (tidf2− is a symmetrical tetraiminodiphenolate Robson-type macrocyclic ligand) were prepared from equimolar combinations of [Mg2(tidf)](NO3)2·4H2O, [MoO2Cl2(dmso)2] (for 1) and complex 1 and Cu(ClO4)2·4H2O (for 2) in acetonitrile. Molecular structures of both complexes were determined and showed atypical modes of coordination. A significant observation was the remarkable flexibility of the macrocycle ligand that effectively accommodated the steric demands of metal cations and the packing forces and showed a unique mode of coordination. Spectroscopic (UV-vis and FTIR) and redox properties are discussed.